Prevalencia del parasitismo intestinal en escolares del caserío Paruque Alto, Julcán, (La Libertad, Perú), en relación al estado nutricional, Julio-Octubre 2018 - GUTIÉRREZ LÓPEZ, Linda Noelia (2019)
Intestinal parasitism by protozoa and helminths is a frequent phenomenon in schoolchildren in Peru; however, prevalences in many areas, especially rural areas of the sierra, are not known. The objective of the present investigation was to determine the prevalence of intestinal parasitism in schoolchildren of the Paruque Alto, Julcán, (La Libertad, Peru) farm in relation to the nutritional status between July to October 2018. Faecal samples were examined, one per child, of 100 school children between 5 to 17 years of age, 50 girls and 50 boys, using: direct, with SSF and Lugol, and of technique Teléman’S modified. Technique the nutritional status was determined by measuring the levels of hemoglobin in an automated system and the status of the state through body mass indexes for age (IMC/E), recommended by the World Health Organization. The general prevalence found was 61.0% and the species of protozoa and helminths diseovereds, with their respective prevalences, were: Entamoeba coli, 34%, Blastocystis hominis, 18%, Giardia lamblia 8% and Iodamoeba bütschlii, 4%; Hymenolepis nana, 9% and Fasciola hepatica, 1%. With the post-adjustment hemoglobin screening assessment, it was found that 06 schoolchildren (6%) presented some degree of anemia: mild (4%) and moderate (2%). The BMI/E showed that 5% of children have malnutrition. It is concluded that malnutrition presented by children is not associated (p> 0.05) with the presence of intestinal protozoa and helminths.